Molecular and biochemical analyses of human immunodeficiency virus type 1 vpu protein. - Strebel, K (1989)
We have performed a detailed analysis of the biochemical properties of the human immunodeficiency virus (HIV) type 1 vpu gene product to elucidate its function during virus replication. Our data suggest that vpu is posttranslationally modified by phosphorylation, since a 16-kilodalton phosphoprotein can be specifically immunoprecipitated with both a serum from an HIV-positive individual (HIV-positive serum) and a vpu-specific antiserum. In contrast, our results suggest that vpu is not glycosylated, even though the protein contains a potential glycosylation site. In vitro translation studies demonstrated that vpu is cotranslationally integrated into microsomal membranes, suggesting that vpu is an integral membrane protein. While vpu was found in significant quantities in virus-producing cells, the protein could not be detected in cell-free culture fluids and is therefore most likely not viron associated. Processing of viral precursor proteins was unaffected by the absence of vpu, and no differences were detected in the protein compositions of wild-type and mutant virions. However, virus release from cultures producing vpu-defective virus was found to be delayed, resulting in the intracellular accumulation of viral proteins. Our data suggest that vpu has a function in the release of virus particles from infected cells.